Financial Derivatives as Social Policy beyond Crisis. (October 2014) - Bryan, Dick; Rafferty, Michael
The period since the global financial crisis has seen financial derivatives not only grow quantitatively in financial markets but also expand socially as a calculative logic, giving increasing precision to the concept of capital and hence class relations. The logic of derivatives involves deconstructing 'things' into a spectrum of tradable risks. The article identifies the ways in which this logic is spreading into an increasing range of social, economic and political policy domains. It posits how, through the logic of derivatives, a range of sociological issues can be seen and re-thought through the eyes of financial calculus.